Developing an energy-based poverty line for South Africa - Claire Vermaak; Marcel Kohler; Bruce Rhodes (Journal of Economic and Financial Sciences, 2014)
The issue of energy poverty or the lack of access to modern energy has received increasing attention in the development literature, including specific reference in the UN Millennium Development Goals (MDGs). Measures based on just energy expenditures (‘energy burden’) are shown to be rather inadequate when identifying energy-poor households. This paper uses an access-adjusted energy poverty measure that allows for varying energy efficiencies and access to different fuel types used by sampled households from a 2008/9 Department of Energy survey. Taking three pre-assigned thresholds of household energy use among LSM1-LSM3 households, all the South African provinces are mapped showing spatial incidences of energy poverty for electrified households. It is proposed that these access-adjusted indicators are methodologically more robust and informative for policy than conventional, purely expenditure-based indicators.